The power of CSR : A quantitative study describing the role of CSR in university students’ consumption within the outdoor industry - Westberg, Olivia (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2020)
In recent years Corporate Social Responsibility (CSR) has gained increasing attention from companies, as CSR activities have been seen to increasingly influence consumers’ attitudes, intentions, and behaviors in relation to brands. This study aims to complement existing research, by focusing on how attitudes and purchase intention of university students are affected by CSR activities of companies within the outdoor industry specifically, as previous research has indicated the impact could vary between industries. Understanding the attitudes and intentions of university students can be seen as particularly interesting, as the attitudes and behaviors of early adopters, typically young and educated people, are typically spread to the majority of the population and market. The research was done in a deductive manner, where two research questions were conducted to fulfill the purpose of the study. The research was conducted by using a quantitative study through a questionnaire responded by students at Luleå University of Technology. The statistical analysis is based upon a factor analysis and further a correlation analysis and a hierarchical multiple regression analysis. Results from this study indicate that there is a relationship between university students’ attitudes towards CSR activities of companies within the outdoor industry and purchase intention. Further, the findings concluded this relationship positively. University students with a strong positive attitude towards a company’s CSR activities got a higher intention to purchase. Therefore, CSR activities should be considered as a strategically important opportunity and a tool for companies in the outdoor industry to influence young and educated consumers’ purchase intentions and attitudes towards the company in a positive way.